A Comparison of Ventriculoperitoneal and Ventriculoatrial Shunts in a Population of 544 Consecutive Pediatric Patients. Issue 1 (5th October 2019) - Rymarczuk, George N; Keating, Robert F; Coughlin, Daniel J; Felbaum, Daniel; Myseros, John S; Oluigbo, Chima; Yadav, Bhupender; Sharma, Karun; Magge, Suresh N
Abstract: BACKGROUND: Although ventriculoperitoneal shunts (VPS) remain the first-line option in most instances of pediatric hydrocephalus, the long-term efficacy of ventriculoatrial shunts (VAS) remains unknown. OBJECTIVE: To characterize the long-term outcomes and adverse occurrences associated with both VPS and VAS at our institution. METHODS: The authors retrospectively analyzed all cerebrospinal fluid (CSF) shunting procedures performed over a 13-yr period at a single institution. A total of 544 pediatric shunt patients were followed for at least 90 d (VPS: 5.9 yr; VAS: 5.3 yr). RESULTS: A total of 54% of VPS and 60% of VAS required at least 1 revision. VPS demonstrated superior survival overall; however, if electively scheduled VAS lengthening procedures are not considered true "failures, " no statistical difference is noted in overall survival ( P = .08). VPS demonstrated significantly greater survival in patients less than 7 yr of age ( P = .001), but showed no difference in older children ( P = .4). VAS had a significantly lower rate of infection ( P < .05) and proximal failure ( P < .001). CONCLUSION: VAS can be a useful alternative to VPS when the abdomen is unsuitable, particularly in older children. Although VPS demonstrates superior overall survival, it should be understood that elective VAS lengthening procedures are often necessary, especially in younger patients. If elective lengthening procedures are not considered true failures, then the devices show similar survival.